The increase in temperature overwhelms silver nanoparticle effects on the aquatic invertebrate Limnephilus sp. - Batista, Daniela Miranda (2020)
The effects of silver nanoparticles (AgNPs) have been largely explored, but there is still a lack of knowledge on their effects under the predicted changes in temperature as a consequence of climate change. The aim of the present study was to determine how leaf consumption by invertebrate shredders is affected by dietary exposure to AgNPs and AgNO3 and whether changes in temperature alter such effects. Also, responses of antioxidant enzymes were examined. In microcosms, the invertebrate shredder Limnephilus sp. was allowed to feed on alder leaves treated with AgNPs (5, 10, and 25 mg L−1) and AgNO3 (1 mg L−1) at 10, 16, and 23 °C (6 replicates). After 5 d, the animals were transferred to clean water and allowed to feed on untreated leaves. The higher leaf consumption by the shredder was related to temperature increase and to the contamination of leaves with AgNPs and AgNO3. Results from enzymatic activities demonstrated that AgNP contamination via food induce oxidative and neuronal stress in the shredder: the activities of catalase and superoxide dismutase were positively correlated with total Ag accumulated in the animal body. Moreover, glutathione S-transferase activity was strongly associated with higher temperature (23 °C). Overall results indicated that the effects of toxicants on consumption rates and enzymatic activities are modulated by temperature and suggested that increases in temperature changes the AgNP effects on invertebrate shredder performance.